EXPLORING SHARIA ECONOMIC LAW DYNAMICS IN WAGE SYSTEMS FOR LOADING AND UNLOADING WORKERS AT PANJANG PORT - Pasca Aulia Fadhilatul Hukkam; Khoiruddin; Hasanuddin Muhammad; Muti Aulia Zahrotunnur (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2025)
The wages of workers involved in the loading and unloading goods at Panjang Port, Bandar Lampung City, are the subject of review within the framework of sharia economic law. This research aims to evaluate the wage system's compliance with Islamic economic principles, with a focus on justice, welfare and protection of workers. This research uses a qualitative approach by analysing literature related to Sharia economic principles and Islamic labour law. Data was also collected through interviews with workers, entrepreneurs and legal experts to understand wage implementation in the port context. The results of the analysis show that the wage system at Panjang Port does not fully comply with Sharia economic principles. Although there are efforts to ensure fairness and worker welfare, there is still a need to increase transparency, worker participation in wage setting, and protection of worker rights in accordance with Islamic teachings. In conclusion, reform is needed in the wage system to ensure compliance with sharia economic principles and the welfare of the people.